KEDUDUKAN CAMAT MENURUT UNDANG UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Barhamudin, Barhamudin; Hendra, Hendra (Solusi, 2021)
The research objectives are: Knowing the position, duties and authority of the sub-district head according to Law Number 23 of 2014. Data sources are: Secondary data, namely data obtained from a literature study consisting of: primary legal materials, secondary legal materials, and tertiary legal materials. . : The position and role of the sub-district head needs to be returned to his position as head of the region who carries out attributive functions, also carries out delegative functions, a camat is needed who is able to increase his role in relation to the system and organizational structure, empowerment of sub-district human resources and optimize service functions to the community, roles and functions The camat needs to be directed to an attributive function without neglecting the authority function of the regional head. In the implementation of regional government according to Law Number 23 of 2014 concerning Regional Government, namely the District is no longer a unit of government territory, but as a unit of work or service area. Camat leadership is an important thing that is needed by every level of the organization in realizing the common goal of coordinating all the power and efforts in carrying out all the tasks and responsibilities assigned to it.